2012
DOI: 10.1002/stem.1174
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Shape Microglia Effector Functions Through the Release of CX3CL1

Abstract: Mesenchymal stem cells (MSC) display a remarkable ability to modulate the immune response and protect the central nervous system mainly through the release of soluble factors in a paracrine fashion, affecting the functional behavior of cells in the tissues. Here we investigated the effect of the interaction between MSC and microglia in vitro, and we dissected the molecular and cellular mechanisms of this crosstalk. We demonstrated that MSC impair microglia activation by inflammatory cues through the inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
127
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 54 publications
14
127
0
1
Order By: Relevance
“…We can only speculate that due to the fact that mononuclear phagocytes with various phenotypic polarization are crucial for tissue repair and regeneration [47,48], the MCP-1/CCL2-induced microglia accumulation at the site of tissue injury or inflammation could have a beneficial effect on the repair process. On the other hand, the IL-1b secretion by MGs in the presence of stem cells is consistent with an earlier report [35] and could be explained by two facts. First, IL-1b, as a powerful proinflammatory cytokine, is involved in the ''licensing'' of MSCs necessary to exert their immunosuppressive properties [7].…”
Section: Microglia Activation and Effector Functionssupporting
confidence: 92%
See 3 more Smart Citations
“…We can only speculate that due to the fact that mononuclear phagocytes with various phenotypic polarization are crucial for tissue repair and regeneration [47,48], the MCP-1/CCL2-induced microglia accumulation at the site of tissue injury or inflammation could have a beneficial effect on the repair process. On the other hand, the IL-1b secretion by MGs in the presence of stem cells is consistent with an earlier report [35] and could be explained by two facts. First, IL-1b, as a powerful proinflammatory cytokine, is involved in the ''licensing'' of MSCs necessary to exert their immunosuppressive properties [7].…”
Section: Microglia Activation and Effector Functionssupporting
confidence: 92%
“…inflammatory (M1-like) into an anti-inflammatory (M2-like) phenotype [26,31,36] mainly through COX-2 mediated production of PGE2 and possibly some other soluble factors [35,37]. Similar PGE2-mediated interaction was also described between other tissue macrophages and MSCs in vitro [12], as well as in vivo [43].…”
Section: Microglia Activation and Effector Functionsmentioning
confidence: 76%
See 2 more Smart Citations
“…A recent study showed that NR4A2 and other neuroprotective molecules can "calm" microglia after the intervention of mesenchymal stem cells and the release of CX3CL1 (Giunti et al, 2012).…”
Section: Discussionmentioning
confidence: 99%